Da live no Facebook para o rádio: a interação entre o ouvinte e a emissora para a construção do debate no programa Toque Esportivo. - Balacó, Bruno Anderson Ferreira (2021)
This research aims to characterize the interaction of listenersinternet users in sports radio programs, based on the use of the comment space in live broadcasts on Facebook. The discussion is inserted in the context of the expanded and hypermedia radio (LOPEZ, 2010; KISCHINHEVSKY, 2016) and the network conversations (RECUERO, 2012) expressed by the audience through digital platforms. As part of a study, we analyzed the experience of the program Toque Esportivo, from the radio O POVO / CBN, in Fortaleza, a sports round tablerecognized for the regular opening of spaces for the participation of the public. In this study, we seek to understand the filters that act in the selection process of these audience contributions, where gatekeeping (MONTE, 2019), gatewatching (CHAGAS, 2019) and newsmaking (SILVA, 2014) processes in the routine of radio broadcasting operate. As a guiding question of the research, we seek to know how the comments posted by the audience on Facebook lives are presented and incorporated in the air. To answer this question, we used a methodology with a multimethod approach (KISCHINHEVSKY et. Al, 2015), using Content Analysis tools (BARDIN, 2004) and the Case Study (DUARTE, 2008). After defining the categories of analysis of the empirical material, we seek to understand the dynamics of the interactive process of the program from five interpretive axes: a) space for the listener, b) The newscaster filter and editorial control, c) The filter of the communicators, d) The importance of image in the interaction process and e) The conflict in sports interaction.